2017
DOI: 10.1186/s13012-017-0570-3
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical analysis of the barriers and facilitators to the implementation of school-based physical activity policies in Canada: a mixed methods scoping review

Abstract: BackgroundGiven the potential impact school-based daily physical activity (DPA) policies can have on the health outcomes of Canadian children, it is surprising that such little research has examined the implementation and student-level effectiveness of these policies, and that even less have used theory to understand the barriers and facilitators affecting uptake of this policy by teachers. This review descriptively summarizes the implementation status, approaches used to implement DPA, and the effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 50 publications
4
45
0
Order By: Relevance
“…The challenges identified in this study also reflect previously identified barriers and facilitators to implementing physical activity interventions across a range of settings, and using a variety of methods 21,22,25 . For example, the key factors that experts identified as influencing the implementation of physical activity interventions in youth‐serving organisations 20 – including: available facilities, equipment, space and staff; competing programs; engaging intervention staff; provider belief, motivation, knowledge and skills about the intervention; and [program] adaptability – all align closely with the more important challenges (i.e.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The challenges identified in this study also reflect previously identified barriers and facilitators to implementing physical activity interventions across a range of settings, and using a variety of methods 21,22,25 . For example, the key factors that experts identified as influencing the implementation of physical activity interventions in youth‐serving organisations 20 – including: available facilities, equipment, space and staff; competing programs; engaging intervention staff; provider belief, motivation, knowledge and skills about the intervention; and [program] adaptability – all align closely with the more important challenges (i.e.…”
Section: Discussionsupporting
confidence: 61%
“…Although most published physical activity research has explored the frequency, patterns, correlates or predictors of physical activity, 19 more recent studies explore the barriers and facilitators to implementing physical activity interventions 20–26 . This research was conducted across a range of settings including schools, 25 youth‐serving organisations, 20 and healthcare settings 26 .…”
mentioning
confidence: 99%
“…Facilitators and challenges can occur in the support , delivery , and/or knowledge synthesis systems (Weatherson, Gainforth, & Jung, ), and each of these were experienced during the At Home/Chez Soi initiative. Regarding the knowledge synthesis system, having clearly communicated principles (or “key ingredients”) that were adaptable to local contexts made the HF model appealing and facilitated implementation (Nelson et al., ).…”
Section: Implementation Sciencementioning
confidence: 99%
“…Another important aspect of implementation science theory is the identification of facilitators and barriers to implementation (Weatherson, Gainforth & Jung, ). Damschroder et al.…”
Section: Supporting Early Implementation Of Housing First In Canadamentioning
confidence: 99%